2013
DOI: 10.1260/1756-8293.5.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Global-Local Optimization of Flapping Kinematics in Hovering Flight

Abstract: The kinematics of a hovering wing are optimized by combining the 2-d unsteady vortex lattice method with a hybrid of global and local optimization algorithms. The objective is to minimize the required aerodynamic power under a lift constraint. The hybrid optimization is used to efficiently navigate the complex design space due to wing-wake interference present in hovering aerodynamics. The flapping wing is chosen so that its chord length and flapping frequency match the morphological and flight properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…4), recapture energy lost to the wake. This phenomenon is usually referred as wake capture which is a well-established mechanism observed in hovering flights of insects and humming birds (14,46,47) . The wake shed behind a flapping wing contains energy provided to the surrounding fluid in the form of momentum and heat.…”
Section: Flapping Wings In Formation Flightsmentioning
confidence: 99%
See 1 more Smart Citation
“…4), recapture energy lost to the wake. This phenomenon is usually referred as wake capture which is a well-established mechanism observed in hovering flights of insects and humming birds (14,46,47) . The wake shed behind a flapping wing contains energy provided to the surrounding fluid in the form of momentum and heat.…”
Section: Flapping Wings In Formation Flightsmentioning
confidence: 99%
“…UVLM has the capability to capture unsteady effects associated with the previously-shed wake vorticity, as well as wake-capture effects, both of which present important aerodynamic aspects in formation flights. Several research efforts have concluded favorably as to the appropriateness of UVLM for preliminary flapping wing design studies for cruise configurations where there is no flow separation nor substantial wing-wake interactions (32)(33)(34)(35)(36)(37)(38)(39) . In a recent paper, Persson et al (38) showed through a detailed comparison between UVLM and higher-fidelity computational fluid dynamics simulations for flapping flight that the UVLM schemes produce accurate results for attached flow cases and even remain trend-relevant in the presence of flow separation.…”
Section: Introductionmentioning
confidence: 99%
“…The third group involves studies (e.g. Sane & Dickinson 2001;Berman & Wang 2007;Ghommem et al 2013;Zheng, Hedrick & Mittal 2013;Nakata, Liu & Bomphrey 2015) investigating optimal 3-D flapping-motion waveforms. Studies from the first group have been primarily inspired by fish-like propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…12 Milano and Gharib 13 combined a GA with water towing tank experiments to identify the maximum average lift force. Ghommem et al 14 conducted kinematic optimization of a hovering flight to minimize the power consumption by linking two dimensional vortex lattice approach and the globallocal optimization methods. The above approaches are restricted by two-dimensional due to low computational efficiency resultant of stochastic analysis.…”
Section: Introductionmentioning
confidence: 99%